Application of Apoptosis to Cancer Treatment - Sluyser, Mels.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Novel drugs are being developed which interact with the programmed cell death (apoptotic) machinery in cancer cells, thereby causing these cells to commit suicide and to be removed from the body. Research is also directed to investigate why the cancer cells sometimes lose the ability to undergo apoptosis after a certain period of time and methods are being developed to reactivate this cell death process. This book is intended for workers in the field and clinicians as a useful guide of the state of affairs in this exciting field which may offer more effective possibilities for treatment of cancer patients. Mels Sluyser is the Editor of the journals APOPTOSIS and ANTI-CANCER DRUGS. He brings together a collection of papers written by the world$1 (Bs leading experts in these fields.s
Disfunction of the Apoptotic Pathway in Cancer Cells -- Calcium Signaling and Apoptosis Resistance of Cancer Cells -- Cell Clearance and Cancer -- Specific, Pro-Poptotic Cell-Signaling: Design of Novel, Recombinant Targeted Antitumor Agents Operating Exclusively Through Modulation of Cellular Apoptotic Events -- Targeting Oncogenes Which Regulate Apoptosis -- Targeting Cyclins to Cause Cancer Cell Apoptosis -- Apoptosis Induction By Tumor- Targeted Toxins -- Targeting Cell-Death Pathways in Multiple Myeloma: Therapeutic Implications -- Cephalostatin 1-Induced Apoptosis in Tumor Cells -- Hamlet; A Novel Tool to Identify Apoptotic Pathways in Tumor Cells -- Cancer Immunotherapy: On the Trail of a Cure? -- Histone Deacetylase Inhibitors as a Treatment of Trail-Resistant Cancers -- Basis of Cell Kill Following Clinical Radiotherapy -- Imaging of Apoptotic Cells in vivo -- Apoptosis-Inducing Anticancer Drugs in Clinical Trials.
Keywords: Medicine; Pharmacy; Cancer research; Molecular biology; Pharmacology; Life sciences; Biomedicine; Cancer Research; Biomedicine general; Molecular Medicine; Pharmacology/Toxicology.; Pharmacy; Life Sciences, general; Electronic books